PENYULUHAN KELUARGA BERENCANA PADA MASA NIFAS DI LINGKUNGAN WILAYAH KERJA PUSKESMAS BINJAI ESTATE TAHUN 2023: community dedication ; Family Planning Counseling; Postpartum Period - sinaga, eliza Bestari (Universitas Aufa Royhan Di Kota Padangsidipuan, 2023)
ABSTRACT The family planning program is an integral part of the national development program and aims to create economic, spiritual and socio-cultural welfare of the Indonesian population in order to achieve a good balance with national production capabilities. The number of children in a family that is considered ideal is two children. The family planning program is one of the efforts that can be made to control the number of children in a family. Family planning is a movement to form healthy and prosperous families by limiting births, so as to control population growth. Birth restriction that can be done is to use contraceptives. According to the Ministry of Health of the Republic of Indonesia, for the past 10 years the family planning program has not been successful enough to reduce the birth rate. This occurs because of the failure of the KB program that is running. Some of the factors that cause the failure of the family planning program include miscalculating the fertile period and forgetting the contraceptive schedule, so we lecturers together with students from Akbid kholisatur Rahmi Binjai want to provide counseling for family planning programs in the Working Area of the Binjai Estate Health Center.